2019
DOI: 10.1007/s42729-019-00118-8
|View full text |Cite
|
Sign up to set email alerts
|

Rotation and Organic Fertilizers Stabilize Soil Water-Stable Aggregates and Their Associated Carbon and Nitrogen in Flue-Cured Tobacco Production

Abstract: Long-term mono-cropping and excessive chemical fertilizer application reduce water-stable soil aggregate stability and soil N and C stocks in tobacco production. This study tested the hypothesis that rotation and fertilizer type affected the proportion of water-stable aggregates and aggregate-associated soil organic carbon (SOC) and total soil nitrogen (TSN) concentrations. Two planting systems (tobacco mono-cropping and tobacco-maize rotation) with five fertilizer treatments (0 and 75 kg N ha −1 , 450 kg oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…The above phenomenon may be related to the following mechanisms viz., after the land-use was converted from annual crops to perennial grasses, the less physical disturbance from plowing and other agricultural activities are beneficial for the formation of soil macroaggregation (Six et al 2000b;Bhattacharyya et al 2009;Liang et al 2002;Plante and McGill 2002). In the study, it is furtherly showed that low N levels including N 1 (51.75 kg ha −1 ) and N 2 (103.5 kg ha −1 ) treatments were beneficial for the formation of soil macroaggregates;the results may be related to the following mechanisms viz., (1) Under low N application levels (N 1 and N 2 ), biological N fixation by alfalfa could provide more nitrogen and substrate for plant and microbial growth (Yu et al 2017); it is favorable for the growth and metabolism of microorganisms, and the decomposition of the original soil organic matter (SOM) can produce positive excitation effects to accelerate mineralization and decomposition, and therefore, more soil labile organic matter such as fungal hyphae and fine roots are produced, which is consistent with the previous research (Chen et al 2020). 2According to the widely used hierarchical theory of aggregate formation, the cementing or binding agents of macroaggregates are relatively labile organic matter fractions, proposed by Tisdall and Oades (1982).…”
Section: Discussionsupporting
confidence: 88%
“…The above phenomenon may be related to the following mechanisms viz., after the land-use was converted from annual crops to perennial grasses, the less physical disturbance from plowing and other agricultural activities are beneficial for the formation of soil macroaggregation (Six et al 2000b;Bhattacharyya et al 2009;Liang et al 2002;Plante and McGill 2002). In the study, it is furtherly showed that low N levels including N 1 (51.75 kg ha −1 ) and N 2 (103.5 kg ha −1 ) treatments were beneficial for the formation of soil macroaggregates;the results may be related to the following mechanisms viz., (1) Under low N application levels (N 1 and N 2 ), biological N fixation by alfalfa could provide more nitrogen and substrate for plant and microbial growth (Yu et al 2017); it is favorable for the growth and metabolism of microorganisms, and the decomposition of the original soil organic matter (SOM) can produce positive excitation effects to accelerate mineralization and decomposition, and therefore, more soil labile organic matter such as fungal hyphae and fine roots are produced, which is consistent with the previous research (Chen et al 2020). 2According to the widely used hierarchical theory of aggregate formation, the cementing or binding agents of macroaggregates are relatively labile organic matter fractions, proposed by Tisdall and Oades (1982).…”
Section: Discussionsupporting
confidence: 88%
“…The first is that the microbes in the TCM application competed with the indigenous rhizosphere bacteria, changing the indigenous rhizosphere bacterial communities, which enhanced the rhizosphere nutrient cycle (Mann et al 2019). The change in the soil physicochemical properties supports this idea (Chen et al 2020); however, further investigations are needed. The second possible explanation is that bacterial strains produced bioactive compounds, mobilizing the fixed or unavailable P, K and Fe in the soil (Rashid et al 2016), which might positively influence soil fertility.…”
Section: Discussionmentioning
confidence: 98%
“…The change in the soil physicochemical properties supports this idea (Chen et al . 2020); however, further investigations are needed. The second possible explanation is that bacterial strains produced bioactive compounds, mobilizing the fixed or unavailable P, K and Fe in the soil (Rashid et al .…”
Section: Discussionmentioning
confidence: 99%
“…Existing reports have suggested that rotation cropping is a valuable management practice that can lower the C footprint of crop production 7 and increase the accumulation of C and N in soil 11,15 ; this result was partly con rmed in the current study, as it was found that the crop system rotation with certain winter crops (RP and RC) increased both SOC and TN stocks within the 0-50 cm depth by 15.29-19.67% and 18.54-20.40%, respectively, compared to that in RF (Table 1). However, the soil C and N stock responses to cropping systems were in uenced by the selection of winter crops.…”
Section: Discussionmentioning
confidence: 99%